Different Cell Types In the Lower Respiratory Tract of the Reindeer (Rangifer tarandus tarandus L.) - A Transmission Electron Microscopical Study - Saari, Seppo A.m. (Rangifer, 1997)
The epithelium of the trachea and distal airways of 12 healthy adult reindeer were studied with transmission electron microscopy. The ultrastructure of the reindeer respiratory tract corresponded to the findings of previous investigators studying other mammalian species. The epithelium of the trachea and bronchi, down to the level of the distal bronchioli, was composed of three main types of cell: ciliated, goblet, and basal. In the distal brochioli, non-ciliated cells similar to those known as Clara cells were predominant. Numerous electron-dense granules and the cell organelle pattern resembled the Clara cell type observed in laboratory rodents, rabbit, sheep, pig, horse, and llama. Pneumocyte 1 and pneumocyte 2 cells were readily identified in the alveoli. The pneumocyte 2 cells possessed short microvilli and granules with lamellar content. Micropinocytotic vesicles were very numerous in the alveolar wall, and a small number of alveolar macrophages occasionally seen in the alveolar lumen.